PENGARUH WHISTLEBLOWING, KOMPETENSI SUMBER DAYA MANUSIA DAN INTERNAL CONTROL SYSTEM TERHADAP PENCEGAHAN FRAUD DANA PSR - andini (Jurnal Agro Indragiri, 2023)
Peremajaan Sawit Rakyat (PSR) is a program to help smallholders renew their oil palm plantations with more sustainable, quality palm oil, reducing the risk of illegal land clearing. In an effort to prevent fraud / fraud of PSR funds, BPDKS distributes funds through escrow accounts of plantation institutions. This is for transaction security. Furthermore, in the implementation of PSR, an audit was carried out by BPK and Sucofindo as institutions appointed by BPDPKS. Fraud prevention can be influenced by several factors such as whistleblowing, human resource competence and internal control system. Whistleblowing as disclosure of unlawful acts, unethical and immoral acts or other acts that can cause losses to the organization and stakeholders. The purpose of this study is: To determine the effect of whistleblowing on Fraud Prevention, HR Competence and Internal Control System affect Fraud Prevention. Research variables (whistleblowing, human resource competence and internal control system) with a total of 52 samples. Descriptive statistical analysis is used to determine the tendency of each research variable. The average whistleblowing score, human resource competence and internal control system were 32.46, 26.96 and 63.77. The average fraud prevention score was 41.25. Based on the results of the study, it can be concluded Whistleblowing, Human resource competence and 3. Internal control system affects the prevention of fraud of PSR funds.